Translational aspects of deep brain stimulation for chronic pain - Pagano, Rosana L.; Dale, Camila S.; Campos, Ana Carolina P.; Hamani, Clement (Frontiers in Pain Research, 2023)
The use of deep brain stimulation (DBS) for the treatment of chronic pain was one of the first applications of this technique in functional neurosurgery. Established brain targets in the clinic include the periaqueductal (PAG)/periventricular gray matter (PVG) and sensory thalamic nuclei. More recently, the anterior cingulum (ACC) and the ventral striatum/anterior limb of the internal capsule (VS/ALIC) have been investigated for the treatment of emotional components of pain. In the clinic, most studies showed a response in 20%–70% of patients. In various applications of DBS, animal models either provided the rationale for the development of clinical trials or were utilized as a tool to study potential mechanisms of stimulation responses. Despite the complex nature of pain and the fact that animal models cannot reliably reflect the subjective nature of this condition, multiple preparations have emerged over the years. Overall, DBS was shown to produce an antinociceptive effect in rodents when delivered to targets known to induce analgesic effects in humans, suggesting a good predictive validity. Compared to the relatively high number of clinical trials in the field, however, the number of animal studies has been somewhat limited. Additional investigation using modern neuroscience techniques could unravel the mechanisms and neurocircuitry involved in the analgesic effects of DBS and help to optimize this therapy.